Job Resources as a mediator between management trust climate and employees' well-being: A cross-sectional multilevel approach - Lee, Michelle Chin Chin * (Universiti Sains Malaysia, 2017)
Adopting the notion that environmental factors affect employees, we investigated the importance of management trust climate as a precursor to job resources (i.e. personal development), positive work outcomes (engagement and job performance) and better well-being (i.e. avoidance of burnout and sleeping problems). Because the Malaysian society is considered to have a higher level of trust than other Asian countries, we used a snowball sampling method and recruited 377 employees from 44 private organisations (62% response rate) in Malaysia as participants in the current study. Multilevel analyses revealed that management trust climate led to higher levels of personal development and job performance; however, it showed no relation to sleeping problems. In addition, personal development mediated management trust climate and job performance, whereas engagement mediated personal development and job performance. Higher burnout led to increased sleeping problems. This study showed organisational level to be an antecedent of job resources and its job resource-engagement model. Since trust conveys a soft psychological contract between two parties, organisations should be aware of the ways trust can be cultivated within the organisation, such as by allowing employees to grow and develop their skills. This may be an effective strategy for ensuring that employees are able to grow within their organisations and execute their duties effectively, without reprisals from higher management.